Design, synthesis and biological evaluation of peptidyl-vinylaminophosphonates as novel cysteine protease inhibitors - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Bioorganic & Medicinal Chemistry, 2011)
We report herein, design and synthesis of vinylaminophosphonates, a novel class of compounds as possible cysteine protease inhibitors. The synthesis of vinylaminophosphonates has been accomplished employing Tsuji-Trost reaction as a key step. The synthesized compounds were assayed against papain, a model cysteine protease and some of our synthesized compounds showed IC50 values in the range of 30-54 mu M thereby suggesting that these chemical entities thus could constitute an interesting template for the design of potential novel protease inhibitors. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cysteine; Inhibitor design; Protease inhibitors; synthesis; Tsuji-Trost reaction; Vinylaminophosphonates